ANALISIS ADAB PENGHAFAL AL-QUR'ĀN DALAM KITAB AL-TIBYĀN DAN IMPLIKASINYA TERHADAP PENGUATAN MATERI AJAR PAI DI SEKOLAH - Salsabila Khairunnisa, - (2022)
The ethics of memorizing the Qur'an is one of the current problems. Some research results show that there is behavior that violates ethics by memorizing the Qur'an. This study seeks to examine the etiquette of memorizing the Qur'an written in the book Al-Tibyān Fī Ādabi Ḥamalah Al-Qur'ān by Imām Abū Zakariā Yahya bin Syaraf An-Nawawī. This research is very much needed, because it can not only be used in educational institutions, but also in Islamic boarding schools and also the general public who are memorizing the Qur'an. This research was conducted using a qualitative approach with the method of library research.The data obtained from primary data in the form of the book Al-Tibyān Fī Ādabi Ḥamalah Al-Qur'ān and secondary data in the form of a translation of the book. The results of this study found that there are nine virtues of memorizing the Qur'an and eleven adab that must be possessed by a memorizer of the Qur'an. The results of this study have implications for the importance of continuing PAI material at school by adopting the etiquette of memorizing the Qur'an in this book.